Sinergias nas fusões e aquisições do setor de educação superior no Brasil - Shwartzbaum, Alan David (2012)
Mergers and acquisitions are a relevant phenomenon in the economy, and are becoming increasingly present in Brazil as well. Among the different economic sectors in which acquisitive growth strategies have been implemented, private tertiary education deserves to be highlighted, not only due to the frequency of transactions, but also due to the size of some of them, placing the Brazilian market leaders among the largest institutions of the world. This essay aims at understanding why those companies have been adopting such strategy, instead of simply relying on organic growth. The attempt to answer this question led to the proposal of a hypothesis that suggests that there are economic motivations for this fact. In other words, the hypothesis that the essay wills to test is that there are synergies in the transactions made in the tertiary education sector in Brazil, as well as those synergies have been converted in economic gains for the acquiring companies and their shareholders. In order to do so, this essay firstly presents a literature review on the subject of mergers and acquisitions and also an overview of the Brazilian tertiary education sector, including its evolution, regulation and other relevant information to support a deeper understanding of the studied phenomenon. Then, based on the proposed methodology, the essay focuses on testing its hypothesis, by identifying the specific synergies present in the sector and in the selected companies (Anhanguera, Estácio and Kroton) and by analyzing how these synergies are being translated to their economic results. Finally, based on the evidences generated by such discussions, conclusions regarding the veracity of the hypothesis are provided.